2015
DOI: 10.1371/journal.pntd.0004018
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression and Infection Profiles of Cutaneous and Mucosal Leishmania braziliensis Isolates from the Same Patient

Abstract: BackgroundLeishmaniasis is a complex disease in which clinical outcome depends on factors such as parasite species, host genetics and immunity and vector species. In Brazil, Leishmania (Viannia) braziliensis is a major etiological agent of cutaneous (CL) and mucosal leishmaniasis (MCL), a disfiguring form of the disease, which occurs in ~10% of L. braziliensis-infected patients. Thus, clinical isolates from patients with CL and MCL may be a relevant source of information to uncover parasite factors contributin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 59 publications
(62 reference statements)
3
40
0
Order By: Relevance
“…Proteomic data indicated that prostaglandin F2 α synthase and a putative HSP70 were more abundant in LCL parasites from both patients. These parasites were more virulent in BALB/c mice, and overexpression of prostaglandin F2 α synthase led to an increase in macrophage infection in vitro, as previously observed for L. infantum …”
Section: Potential Applications Of Proteomics In Leishmaniasissupporting
confidence: 74%
See 1 more Smart Citation
“…Proteomic data indicated that prostaglandin F2 α synthase and a putative HSP70 were more abundant in LCL parasites from both patients. These parasites were more virulent in BALB/c mice, and overexpression of prostaglandin F2 α synthase led to an increase in macrophage infection in vitro, as previously observed for L. infantum …”
Section: Potential Applications Of Proteomics In Leishmaniasissupporting
confidence: 74%
“…Until today, there is no proteomic analysis of L. braziliensis from DL. Besides, only one paper has compared proteomes of LCL and ML . In this work, genome, metabolome and proteome of two pairs of parasites isolated from cutaneous and mucosal lesions from the same patient were compared.…”
Section: Potential Applications Of Proteomics In Leishmaniasismentioning
confidence: 99%
“…Since Leishmania is an intracellular parasite in the mammalian host, it has been postulated that migration occurs through infected macrophages, although the mechanisms involved in the preferential location of the disease on the nasal mucosa are not known. 8 We believe that histiocytes or other inflammatory cells targeted by the parasite migrated by proximity to the medial orbital wall and participated and probably contributed to the same granulomatous reaction seen in the oral and nasal mucosae. Since these lesions have a typically low parasite load, it is not surprising that the amastigote forms of the parasite could not be visualized.…”
Section: Discussionmentioning
confidence: 86%
“…An explanation for the biological events responsible for this loss was not addressed in the present study. However, it is important to note that if this viral loss commonly occurs among other Leishmania strains, previous studies using LRV detection exclusively in isolates may have underestimated the rate of viral co-infection for at least some Leishmania species (17, 1921, 25, 2932).…”
Section: Discussionmentioning
confidence: 99%